2016
DOI: 10.1186/s13063-016-1641-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with study attrition in a pilot randomised controlled trial to explore the role of exercise-assisted reduction to stop (EARS) smoking in disadvantaged groups

Abstract: BackgroundStudy attrition has the potential to compromise a trial’s internal and external validity. The aim of the present study was to identify factors associated with participant attrition in a pilot trial of the effectiveness of a novel behavioural support intervention focused on increasing physical activity to reduce smoking, to inform the methods to reduce attrition in a definitive trial.MethodsDisadvantaged smokers who wanted to reduce but not quit were randomised (N = 99), of whom 61 (62 %) completed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…The finding that participation in prior follow-up assessments increased the likelihood of retention at the final assessment is supportive of prior research suggesting maintenance of contact with participants across the follow-up period facilitates retention [33, 50, 51]. Such results suggest that intermediate follow-up assessments not only provide extended behaviour-change data, but serve as a trial design strategy to improve retention at the primary follow-up point.…”
Section: Discussionsupporting
confidence: 78%
“…The finding that participation in prior follow-up assessments increased the likelihood of retention at the final assessment is supportive of prior research suggesting maintenance of contact with participants across the follow-up period facilitates retention [33, 50, 51]. Such results suggest that intermediate follow-up assessments not only provide extended behaviour-change data, but serve as a trial design strategy to improve retention at the primary follow-up point.…”
Section: Discussionsupporting
confidence: 78%
“…Illustrating a consensus regarding the need to consider and address the issue of low retention in clinical and health behaviour trials: the inclusion of items on participant retention in the Consolidated Standards of Reporting Trials (CONSORT) statement,28 29 and prioritisation of trial methodology research to develop novel approaches to increase retention in randomised trials 30 31. In addition, the emergence of recent systematic reviews examining retention rates in health behaviour studies32–36 and publication of retention data from high quality randomised trials37–39 indicates increased interest in the topic of retention and a recognition of its importance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found several factors to be associated with lower attrition rates, including older participant age, being followed up by telephone call, smoking relapse or failure to reduce smoking levels. (11) To reduce dropout rates in future studies, strategies to engage younger participants should be followed and reassurances given to participants that smoking behaviour should not influence ongoing participation in the study. (11) When participants are followed up by telephone calls, researchers should work flexible hours, so that those who are employed can be contacted during regular working hours.…”
Section: Discussionmentioning
confidence: 99%
“…(11) To reduce dropout rates in future studies, strategies to engage younger participants should be followed and reassurances given to participants that smoking behaviour should not influence ongoing participation in the study. (11) When participants are followed up by telephone calls, researchers should work flexible hours, so that those who are employed can be contacted during regular working hours. (11) At our centre, we have reduced fees for follow-up appointments to reduce the financial load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation